Experimental and Constitutive Model Study on Dynamic Mechanical Behavior of Metal Rubber under High-Speed Impact Loading. (28th February 2021) - Zou, Youchun; Xiong, Chao; Yin, Junhui; Cui, Kaibo; Zhu, Xiujie; Deng, Huiyong; Song, Shijun
Abstract : The development of lightweight, impact-resistant, and high energy-consuming materials is of great significance for improving the defense capabilities of military equipment. As a new type of damping material, metal rubber has demonstrated great potential for application in the field of impact protection. In this paper, the dynamic mechanical response of metal rubber under a high strain rate is studied, which provides a new idea for developing high-performance protective materials. The stress-strain curves, energy absorption performance, and wave transmission performance of metal rubber at various strain rates were investigated based on a split-Hopkinson pressure bar (SHPB) device. The dynamic stress-strain curve of metal rubber is divided into three stages: elastic stage, plastic stage, and failure stage. The optimal energy absorption efficiency is greater than 0.5, and the maximum value can reach 0.9. The wave transmittance is less than 0.01. The dynamic mechanical tests have proved that metal rubber has excellent energy absorption capacity and impact resistance property. A constitutive model based on Sherwood–Frost was established to predict the dynamic mechanical behavior of metal rubber. The results of comparison between the calculation and the experiment show that the constitutive model can accurately predict the dynamic mechanical performance of metal rubber.